2020
DOI: 10.1055/s-0040-1705181
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Vasopressor Therapy for Pediatric Septic Shock: When Is Too Much?

Abstract: It is unknown if the requirement for high dose of vasopressor (HDV) represents a poor outcome in pediatric septic shock. This is a retrospective observational analysis with data obtained from a single center. We evaluated the association between the use of HDV and survival in these patients. A total of 62 children (38 survivors and 24 nonsurvivors) were assessed. The dose of vasopressor (hazard ratio 2.06) and oliguria (hazard ratio 3.17) was independently associated with mortality. The peak of vasopressor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Vasopressor drugs have a log‐linear dose response curve, with decreasing incremental effectiveness at higher doses and likely a greater potential for toxicity 13 . A cutoff of 1.3 μg/kg/min of vasopressor infusion was found to be associated with mortality with a sensitivity of 75% and specificity of 89% in pediatric patients with septic shock 7 . So may be our cutoff for high‐dose vasopressor therapy was low and further research are warranted to define cutoff for high‐dose vasopressor therapy for non extubation in OR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vasopressor drugs have a log‐linear dose response curve, with decreasing incremental effectiveness at higher doses and likely a greater potential for toxicity 13 . A cutoff of 1.3 μg/kg/min of vasopressor infusion was found to be associated with mortality with a sensitivity of 75% and specificity of 89% in pediatric patients with septic shock 7 . So may be our cutoff for high‐dose vasopressor therapy was low and further research are warranted to define cutoff for high‐dose vasopressor therapy for non extubation in OR.…”
Section: Discussionmentioning
confidence: 99%
“…Sahinturk 1 et al found high‐dose vasopressor as risk factor for not extubation in OR but they did not describe what is high‐dose vasopressor therapy in pediatric patients. We defined high‐dose vasopressor therapy as either 2 vasoactive medicines required to maintain blood pressure or noradrenaline dose more than 0.3 μg/kg/min 7 . Fullington 11 et.al also did not extubated the patient who were on >1 vasopressor during time period (2005–2008); however, they started extubating patients with more than 1 vasopressor during time period (2008–2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient's condition progresses rapidly and poses a serious threat to the safety of patients. The basic pathological features of the patients were systemic vascular dilatation and increased capillary permeability, showing insufficient circulating blood volume, reduced tissue perfusion, and systemic metabolic disorder [ 1 ]. Accurate evaluation of tissue perfusion for patients with septic shock is of great significance for guiding clinical treatment, and the prognosis of patients' needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%